In Vitro Propagation Studies On Coleus Forskohlii Briq. - A Medicinal Plant - R. PRAVEENA; S. AMARNATH PANDIAN; M. JEGADEESAN (International Journal of Pharma and Bio Sciences, 2012)
Coleus forskohlii Briq. (Lamiaceae) is an important medicinal plant with excellent export potential in herbal drug trade. The root of this plant is medicinally useful for high blood pressure, spasmolysis, obesity and constipation. A diterpene compound, forskolin, obtained from tubers root of this plant is used for glaucoma congestive, asthma and certain cancers. The present work aims at evolving a protocol for rapid multiplication using culture technique. Tissue explants from leaf lamina, leaf base and node were cultured on MS medium supplemented with different concentrations (0.5-2.0 mg/l) of IAA, 2, 4-D and BAP and their growth responses like callusing, and shooting and rooting were elucidated. It was observed that leaf base explants elicited maximum callusing, shooting and rooting response than that of node and leaf lamina. Multiple shoots were obtained from leaf base explants. This indicates the possibility of using tissue culture protocol for commercial scale of production.